Effects of adipokines and obesity on uterine contractility. (April 2017) - Azaïs, Henri; Leroy, Audrey; Ghesquiere, Louise; Deruelle, Philippe; Hanssens, Sandy
Graphical abstract: Highlights: Obesity is associated with alterations in the quality of labor. Functional changes and their consequences can be attributed to a disruption of hormonal balance encountered in obese women and involving adipokines. Better knowledge of the impact of obesity on labor and delivery pathophysiology should provide a suitable and effective management. Abstract: Obesity is a major public health problem. The prevalence of obesity has significantly increased in developed countries, particularly in France with an overall increase of 76% over the last 15 years. In pregnant women, obesity is associated with alterations in the quality of labor, such as delayed onset of labor, a higher rate of prolonged pregnancies, prolonged labor, and higher oxytocin requirements. There is also an increased prevalence of Cesarean sections, particularly during the active phase of labor, and perinatal complications (postpartum hemorrhage). It seems that some of these functional changes and their consequences can be attributed to a disruption of hormonal balance encountered in obese women and involving adipokines (apelin, ghrelin, visfatin, leptin), but also to the interactions between adipose tissue and the "oxytocin (OT) – oxytocin receptor (OTR)". In this review, we detailed mechanisms to understand the impact of specific metabolic alterations in obesity on uterine contractility. Better knowledge of the impact of obesity on labor and delivery pathophysiology should strengthen the prevention of obesity in women of childbearing age and provide a suitable and effective management. The beneficial effect of weight loss and exercise in non-pregnant women on the correction of metabolic disorders secondary to obesity should be studied in populations of overweight women to demonstrate its effectiveness.